2019
DOI: 10.6061/clinics/2019/e966
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of different surgical approaches for pediatric cataracts: complications and rates of additional surgery during long-term follow-up

Abstract: OBJECTIVES: To compare long-term postoperative complications of pediatric cataract surgery with primary intraocular lens (IOL) implantation associated with posterior capsulotomy (PC) and anterior vitrectomy (AV) between patients treated with a corneal or pars plicata/pars plana approach. METHODS: Children who underwent cataract surgery with in-the-bag primary IOL implantation were divided into two groups according to PC and AV surgical approach: a corneal approach (grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Although posterior capsulotomy and anterior vitrectomy were performed via the pars plana approach (12) with in-the-bag IOL implantation in all patients, almost 14% of the children developed VAO in this study. We noted that, over time, a large capsulotomy is required to reduce VAO.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although posterior capsulotomy and anterior vitrectomy were performed via the pars plana approach (12) with in-the-bag IOL implantation in all patients, almost 14% of the children developed VAO in this study. We noted that, over time, a large capsulotomy is required to reduce VAO.…”
Section: Discussionmentioning
confidence: 78%
“…Although advances in IOL designs and surgical techniques have led to lower rates of visual axis opacification (VAO), VAO continues to be frequently observed in children; its incidence is higher in children than adults (12) . At younger ages, the higher number of mitotically active cells results in faster growth of the residual lens epithelial cells remaining after surgery (6,(13)(14)(15) .…”
Section: Introductionmentioning
confidence: 99%
“…An incidence of 28% of corectopia was described in patients who underwent surgery before 7 months of age using different techniques (3) . Comparing the anterior and posterior approaches for capsulotomy and vitrectomy in pediatric cataracts with primary IOL implant, in patients aged 3 months to 9 years old, the authors found more complications in the anterior approach (9) . No corectopia or vitreous tag was detected as a postoperative complication in this study.…”
Section: Discussionmentioning
confidence: 96%
“…The IATS study reports 7% and 14% glaucoma or glaucoma suspect in the first and fifth follow-up year respectively, excluding patients with corneal diameter less than 10 mm in which the incidence of glaucoma is significantly higher, but including patients with persistent fetal vasculature (PFV). PFV presented a risk 3.1 higher than eyes without this condition in the first follow-up year (7)(8)(9)(10)(11)(12)(13)(14)(15) . In the IoLunder2 study, the incidence of glaucoma or persistent ocular hypertension was approximately 30%; however, in this study, one-third of the patients had some ocular anomaly, including corneal diameter less than 10 mm and PFV (16) .…”
Section: Discussionmentioning
confidence: 99%
“…However, the visual outcome is largely dependent on the timing of surgery once a dense cataract occurs ( Lim et al, 2017 ). Most vision loss associated with congenital cataract is due to amblyopia ( Mansouri et al, 2013 ), and others are due to postoperative complications such as secondary glaucoma and retinal detachment either from birth or in early infancy ( Chak and Rahi, 2008 ; Koch et al, 2019 ; Wang et al, 2020 ). The pathogenesis of congenital cataract can be divided into genetic, environmental, and unknown causes.…”
Section: Introductionmentioning
confidence: 99%